Modulation of the Work Function by the Atomic Structure of Strong Organic Electron Acceptors on H‐Si(111). (18th March 2019) - Wang, Haiyuan; Levchenko, Sergey V.; Schultz, Thorsten; Koch, Norbert; Scheffler, Matthias; Rossi, Mariana
Abstract: Advances in hybrid organic/inorganic architectures for optoelectronics can be achieved by understanding how the atomic and electronic degrees of freedom cooperate or compete to yield the desired functional properties. Here, how work function changes are modulated by the structure of the organic components in model hybrid systems is shown. Two cyano‐quinodimethane derivatives (F4‐TCNQ and F6‐TCNNQ), which are strong electron‐acceptor molecules, adsorbed on H‐Si(111) are considered. From systematic structure searches employing the range‐separated hybrid HSE06 functional including many‐body van der Waals (vdW) contributions, it is predicted that, despite their similar composition, these molecules adsorb with significantly different densely packed geometries in the first layer, due to strong intermolecular interaction. F6‐TCNNQ shows a much stronger intralayer interaction (primarily due to vdW contributions) than F4‐TCNQ in multilayered structures. The densely packed geometries induce a large interface‐charge rearrangement that results in a work function increase of 1.11 and 1.76 eV for F4‐TCNQ and F6‐TCNNQ, respectively. Nuclear fluctuations at room temperature produce a wide distribution of work function values, well‐modeled by a normal distribution with σ = 0.17 eV. These findings are corroborated with experimental evidence of pronounced island formation for F6‐TCNNQ on H‐Si(111) and with the agreement of trends between predicted and measured work function changes. Abstract : The adsorption of strong electron acceptors (F4‐TCNQ/F6‐TCNNQ) on H‐Si(111), a model hybrid organic–inorganic system for studying optoelectronics, is investigated. The strong intermolecular intralayer attraction of F6‐TCNNQ molecules acts as the driving force for forming tall multilayer islands, which is corroborated by experiment. Finite‐temperature nuclear fluctuations are found to cause electronic frontier‐orbital broadening far larger than the thermal energy.